Fast detection of protein kinase B in chrysin treated colorectal cancer cells using a novel multicore microfiber biosensor - Zhen Tian; Hongzhuan Xuan; Yicun Yao; Shengyu Hao; Zhichao Zhang; Bingyuan Zhang; Jingao Zhang; Liqiang Zhang; Xinzhu Sang; Jinhui Yuan; Gerald Farrell; Qiang Wu (Communications Engineering)
Abstract Rapid and accurate determination of target proteins in cells provide essential diagnostic information for early detection of diseases, evaluation of drug responses, and the study of pathophysiological mechanisms. Traditional Western blotting method has been used for the determination, but it is complex, time-consuming, and semi-quantitative. Here, a tapered seven-core fiber (TSCF) biosensor was designed and fabricated. By immobilizing protein kinase B (PKB), also known as AKT, antibody onto TSCF surface, the microfiber biosensor can be used for quantitatively detecting the AKT level in solution concentrations as low as 0.26 ng/mL. To test the reliability of the TSCF sensing method in a medical application, the TSCF biosensor was used to study the relationship between chrysin’s anticancer effect and the concentration of AKT in a human colorectal cancer cell line (LoVo cells). The results reveal that the inhibitory effect of chrysin on LoVo cells is positively correlated with the dose, agreeing well with the equivalent results using the traditional Western blotting method.